EVALUATION OF THE EFFECT OF ETHANOLIC LEAF EXTRACT OF SOLENOSTEMON MONOSTACHYUS ON BLOOD GLUCOSE AND LIVER ENZYMES IN STZ INDUCED DIABETIC RATS - Edet, Asanga; Amaechi, Dennis; Udosen, E. O.; Uboh, F. E. (European Scientific Journal, ESJ, 2015)
Diabetes mellitus as a metabolic disorder is known to affect the metabolism of carbohydrate, lipids as well as protein. The myriad devastating symptoms arising from this endocrine disorder is of paramount concern to many scientists who believe that traditional medicine could be the solution to the many years of looking for an antidiabetic drug that is easily accessible, reliable, cost effective with minimal side effect for the treatment of diabetes mellitus, hence, this study was designed to unravel the effect of ethanolic leaf extract from a medicinal plant: Solenostemon monostachyus on blood glucose and liver enzymes in STZ-induced diabetic albino wistar rats. A total of 24 rats were used for the experiments and were divided into four groups (i.e. diabetic control (DC), normal control (NC), Insulin treated (INS) and Solenostemon monostachyus (SM) treated groups), with 6 rats each. The extract, 250 mg/kg body weight, was administered twice daily for 21 days. The serum glucose level in mg/dL was 70.00 ± 10.50 for SM treated groups, 256.00 ± 15.00 for DC. There was significant decrease at p < 0.05 in blood glucose level of rats administered with the extract within this period. The results of the ALT and AST levels in U/L were 13.37 ± 2.08 and 12.38 ± 5.10 for DC, and 7.20 ± 0.19 and 6.50 ± 1.46 for SM treated groups respectively, hence, SM significantly reduced at p < 0.05 the level of AST and ALT when compared with the control group. Therefore, it may be concluded that the ethanolic leaf extract of SM may have hypoglycaemic and hepatoprotective properties when administered to rats.